Pertautan Citra Tampak Atas dengan Metode Stereoskopik untuk Menghilangkan Distorsi Perspektif - Endang Pertiwi; Bambang Nurcahyo Prastowo; Lukman Awaluddin (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2019)
Stitching citra with different object’s depth and disposed close to the camera willing caused panoramic citra with distortion perspective (caused double or disappear object) because the camera see in two dimension with large horizontal disparity by each camera. For solve that problem, stereoscopic method purpose to give depth perception of three dimension from two images with same background so information of depth by the object be able to get with intuitive way.This research presented system with ROI segmentation for any static objects, stitching for each objects and combine them become a panoramic image then shown in citra panoramic. SIFT descriptor used for detect and extract feature from the images. The result of this system successful presented combination for stitching by the static objects.